2008
DOI: 10.1371/journal.pmed.0050044
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Study of Maternal Mortality in Mozambique: The Contribution of Infectious Diseases

Abstract: BackgroundMaternal mortality is a major health problem concentrated in resource-poor regions. Accurate data on its causes using rigorous methods is lacking, but is essential to guide policy-makers and health professionals to reduce this intolerable burden. The aim of this study was to accurately describe the causes of maternal death in order to contribute to its reduction, in one of the regions of the world with the highest maternal mortality ratios.Methods and FindingsWe conducted a prospective study between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
105
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 32 publications
16
105
1
1
Order By: Relevance
“…33 Our study showed that comorbid conditions, such as HIV/AIDS, and diseases of poverty, such as anaemia, contributed to late pregnancy-related deaths after a near miss. Except for direct obstetric complications, HIV infection was the most important contributor to pregnancy-related deaths in our study.…”
Section: Researchmentioning
confidence: 64%
“…33 Our study showed that comorbid conditions, such as HIV/AIDS, and diseases of poverty, such as anaemia, contributed to late pregnancy-related deaths after a near miss. Except for direct obstetric complications, HIV infection was the most important contributor to pregnancy-related deaths in our study.…”
Section: Researchmentioning
confidence: 64%
“…HIV/AIDS is one of the major causes of death among women and children in Mozambique (Menéndez et al, 2008;Sacarlal et al, 2009). The health system and infrastructure in Mozambique do not appropriately reflect the rapid recent changes in social conditions, including the high prevalence of HIV infection (Hagopian et al, 2008).…”
mentioning
confidence: 99%
“…However, recent evidence suggests that the impact of malaria on maternal deaths in sub-Saharan Africa has been under estimated and that MiP may be an important direct cause of maternal mortality. [17][18][19] In a recent autopsic study of maternal deaths carried out in Mozambique, malaria was a direct cause of death in 10% of women, representing the fourth cause of death. 19 The burden of malaria during pregnancy in Africa has been exacerbated by the advent of HIV which increases susceptibility to malaria in pregnancy in all parities, reduces the efficacy of antimalarial interventions and complicates the use of antimalarials due to drug interactions.…”
mentioning
confidence: 99%
“…[17][18][19] In a recent autopsic study of maternal deaths carried out in Mozambique, malaria was a direct cause of death in 10% of women, representing the fourth cause of death. 19 The burden of malaria during pregnancy in Africa has been exacerbated by the advent of HIV which increases susceptibility to malaria in pregnancy in all parities, reduces the efficacy of antimalarial interventions and complicates the use of antimalarials due to drug interactions. 20 Regardless of endemicity or the level of immunity, maternal malaria causes anaemia.…”
mentioning
confidence: 99%